Association between low drying temperature and ozonation process to control pest and preserve the maize quality - Sampson, Uzoma (2022)
Maize is one of the cereals major produced for its nutritional and energy characteristics and that has become one of the most cultivated crop in the world. To maintain high quality maize during storage, due to its hygroscopic nature, proper storage management is needed, to avoid microorganisms and insects’ infestation. Drying has always been the most common method of preserving grains. Drying of agricultural products is important as it creates less favorable conditions for fungi growth. Drying grains can be achieved either using low-temperature or high-temperature air. Ozone is a highly oxidizing agent and it is effective against many types of microorganisms and insects that infest in food. Then, the objectives of the present study were i) to determine the combined effect of different specific flow rates at a low temperature flow in the drying process of maize with ozone; and ii) to determine the quality of grains and the pest infestation exposed to low drying temperature and varying specific flow rates of ozone gas; Yellow maize grains with moisture content of 17.2 g 100g -1 (wet basis, w.b.) were used. For drying process, a cylindrical column made of PVC (0.30 m in diameter and 0.35 m in height) was used. The cylinder column was filled with the maize (5.0 kg), adopting different specific airflow rates: 0.50, 0.82 and 1.05 m 3 min -1 t -1 . The drying air temperature was 22 ±2 °C and relative humidity between 50 and 55%. The inlet ozone concentration was 2.3 mg L -1 . In the control treatment, oxygen was used. The drying of the grains was carried out until achieving a moisture content of ≈12.5%. The residual concentration of ozone was determined during the drying process, at regular intervals. The saturation time and saturation concentration were calculated. The effect of ozone on A. flavus infection and S. zeamais infestation were evaluated. The maize quality after drying was analyzed using electrical conductivity, germination, and color of the grains as the indicators. The experiment was carried out as a completely randomized design, with three replications. The longest saturation time (1.68 days) was observed for specific flow rate of 0.50 m 3 min -1 t -1 . The highest value of saturation concentration was obtained for specific flow rate of 1.05 m 3 min -1 t -1 (2.02 mg L -1 ). The association of ozone with drying at low temperature was efficient in controlling A. flavus, for all specific flow rates. There were no adults of S. zeamais that survived when exposed to ozone during the drying process at low temperature, unlike what was observed in the control treatment (oxygen). There was no significant variation (P>0.05) in the electrical conductivity of the grains as a result of ozonation. It was observed that ozone caused a reduction in the percentage of germination of the grains. As for the color of the grains, there was a significant variation (P<0.05) only concerning the luminosity (L*) and chroma (C*). In the Principal Component Analysis, two ordered groups were formed: a group made of samples submitted to drying at low temperature in the absence of ozone and other group formed by samples subjected to drying at low temperature associated with ozonation. It is possible to conclude that: i) the specific flow rate influences the ozone saturation process during the corn drying process at low temperature; ii) ozone is effective in controlling A. flavus and S. zeamais when associated with corn drying at low temperature, and when specific flows between 0.5 and 1.05 m 3 min -1 t -1 are adopted; and iii) the use of ozone during maize drying at low temperature does not cause changes in quality that could compromise the commercialization of the product. Keywords: Drying. Ozone. Sitophilus zeamais. Aspergillus flavus. Color.